The role of identity in the 2015 Romanian shepherd protests - O'Brien, Thomas; Creţan, Remus (Taylor and Francis, 2018)
Shepherds have a particular place in the history and culture of Romania. For centuries they have had rights to graze their sheep in public pastures and manage their flocks using traditional methods. Changes at the national and European level have threatened this way of life and provoked protest, most recently in December 2015 over plans to limit sheepdog numbers and restrict winter grazing rights. This article draws on interviews with participating and non-participating shepherds to examine the motivations behind the protest action and its relation to their position in contemporary society. The findings suggest how marginalised groups in society are able to draw on folk histories and cultural identities in the formulation of contentious politics in defence of their interests. The post-communist setting of the protests also highlights the persistence of traditional practices during a period of social and political upheaval.
Keywords: Shepherds; protest; Romania; hunting; identity; transhumance